Food Insecurity Screening in Pediatric Clinical Settings: A Caregivers' Perspective. - Barnidge, Ellen; Krupsky, Kathryn; LaBarge, Gene; Arthur, Joshua (Maternal & Child Health Journal, 2020)
Objectives: Food insecurity (FI) has serious academic, social, and physical health consequences for children. A recent clinical recommendation suggests FI screening during child well visits. While FI screening research has considered clinician feedback, little is known about caregivers' experience of disclosing FI to health care providers. Our paper explores caregivers' barriers and facilitators to FI disclosure. Methods: A survey on factors influencing FI disclosure was completed in a pediatric clinic waiting room in St. Louis, MO. Among households with FI, 15 caregivers participated in a qualitative interview. Caregivers were asked about experiences discussing FI with health care providers. We calculated frequencies for survey responses and analyzed interview data using thematic content analysis. Results: Caregivers highlighted stigma, fear of child being taken away, and shame as barriers to FI disclosure. Caregivers identified strong interpersonal skills, open body language, and empathy as facilitators to disclosure at the interpersonal level. Provider initiated conversations, consideration of FI disclosure in the presence of a child, and normalization of FI discussions within the clinic were described as ways to encourage FI disclosure at the organizational level. In response to FI disclosure, caregivers would like providers to offer resources including referrals to community-based resources extending beyond food. Conclusions for Practice: Our study identifies considerations for FI screening in health care settings, spanning the social-ecological model, from the perspective of caregivers. To successfully screen and address FI, multifaceted health care interventions should address barriers and promote facilitators across multiple levels and in consideration of multiple social needs.